Narratives of Women Leaders in Higher Education in Pakistan - Hussam, Saba; Bano Kazimi, Dr. Anjum (JELM, 2025)
This narrative study explores the experiences of eight women leaders. Five from Lahore and three from Karachi educational sector, Pakistan. The study limits itself to the Higher education sector. Criterion sampling is used for the current study as it is among one of the purposeful sampling strategies used for “narrow a range of variation and focus on similarities” (Palinkas et al, 2013). This technique is selected as it is “consistent with the aims and assumption inherent” for a particular method’ (Palinkas et al, 2013). The criteria for sampling was at least 12 years of experience in the field of education in any capacity, be in a leadership position of higher education for at least 5 years, either have a doctoral degree or have state conferred recognition/award in her name. The study aims to answer the essential questions about the barriers faced by these women, opportunities provided to them and their mentorship role for the coming generation. A qualitative methodology is used with tools like in-depth interviews and fact sheet for arriving at the lived experiences of these women in the form of deeply felt narratives. Both ‘analysis of narratives’ and ‘narrative analysis’ is used to gather a complete picture of complex human experiences and narrate them in the form of individual stories and a combined thematic analysis. The study concludes that there is no fixed road map for success in educational leadership which can serve as a blueprint. However, there are over-arching themes like a strong parental support, a broadened vision, higher education and helpful mentors, all of these bring out the best in women to garner their leadership skills. The study also finds barriers like the socio-economic status, a toxic work environment and gender which can hinder the progress of women in Pakistan. However, such barriers can be altered through fortitude, hard work and determination.